2016
DOI: 10.1038/ijo.2016.154
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory environment and role of TNF-α in endometrial function of obese women having polycystic ovarian syndrome

Abstract: These results suggest that the PCOS condition induces an inflammatory state exacerbated when obesity is present, where a higher TNF-α signaling is observed, all of which could affect glucose uptake in the tissue and may cause fertility failures in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 51 publications
3
64
1
Order By: Relevance
“…For instance, uterine TNFα and Il-6 gene expression is increased in PCOS-like rats, confirming that TNFα and Il-6 play inflammatory roles in the endometrial function in PCOS patients (Orostica et al, 2016, Piltonen et al, 2013, 2015). We also show that the anti-inflammatory effect of metformin is via the PI3k-Akt-NFκB signaling pathway.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, uterine TNFα and Il-6 gene expression is increased in PCOS-like rats, confirming that TNFα and Il-6 play inflammatory roles in the endometrial function in PCOS patients (Orostica et al, 2016, Piltonen et al, 2013, 2015). We also show that the anti-inflammatory effect of metformin is via the PI3k-Akt-NFκB signaling pathway.…”
Section: Discussionmentioning
confidence: 60%
“…For example, there is a noticeable increase in the inflammatory cytokines such as IL-6 and TNFα in the peripheral circulation of PCOS patients 50,51 . Similarly, several studies by our laboratory and others have described increased gene expression of IL-6, TNFα, and Mcp-1 (CCL-2) in PCOS patient endometrium and the PCOS-like rat uterus 10,28,[52][53][54] . Moreover, P4 has been shown to suppress TNFα-stimulated IL-6 and Mcp-1 production in human endometriotic stromal cells in vitro 55 .…”
Section: Commentmentioning
confidence: 91%
“…Our data suggest that regulation of uterine ERK1/2 expression in vivo is time-dependent 20-22 , which is similar to the regulation of PGR isoforms and PGR-targeted gene expression. The MAPK/ERK/p38 signaling pathway contributes to the regulation of inflammation and cytokine production 60,61 , and the dysregulation of inflammation-related molecules is associated with PCOS conditions [52][53][54]62 . Furthermore, like the activation of NFκB signaling that induces the transcriptional levels of inflammation-related gene expression in ovarian granulosa cells and in serum in PCOS patients 51,63 , our previous study has shown that the sustained metformin treatment markedly suppresses uterine inflammatory gene expression, especially the Il-6 and TNFα mRNAs that are associated with inhibition of nuclear NFκB translocation in PCOS-like rats 28 .…”
Section: Commentmentioning
confidence: 99%
“…Our data suggest that regulation of uterine ERK1/2 expression in vivo is time dependent (Thienel et al 2002, Lee et al 2013, Tapia-Pizarro et al 2017, which is similar to the regulation of PGR isoforms and PGR-targeted gene expression. The MAPK/ERK/p38 signaling pathway contributes to the regulation of inflammation and cytokine production (Cuadrado & Nebreda 2010, Arthur & Ley 2013, and the dysregulation of inflammation-related molecules is associated with PCOS conditions (Matteo et al 2010, Piltonen et al 2013, Orostica et al 2016. Furthermore, like the activation of NFκB signaling that induces the transcriptional levels of inflammation-related gene expression in ovarian granulosa cells and in serum in PCOS patients (Liu et al 2015, Zhao et al 2015, our previous study has shown that the sustained metformin treatment markedly suppresses uterine inflammatory gene expression, Figure 8 Schematic representation of the actions of metformin on the uterine progesterone signaling in the PCOS-like rats.…”
Section: Esr1mentioning
confidence: 99%